Preparation, characterization and cytotoxic evaluation of novel au(iii) complexes of thioglycolate and 2-mercaptoglycolate ligands - N.A. Al-Omari; N. H.Butrus (University of Mosul, 2013)
Objectives: One of the main goals of the present research is to establish whether any direct correlation exists between the nature of the gold(III) S-ligands and the cytotoxic properties of these compounds. Methods: The gold(III) complexes [Au(L)(L')n]; where L = SCH2COO-; L' = HSCH2COO- , were synthesized according to the reported procedure. The cytotoxic evaluation where done by the exposure of the synthesized compounds to HEP-2 cell line. Results: The cytotoxic evaluation revealed that the HEP-2 cell line differ in its sensitivity toward the selected complexes compared to cisplatin. Conclusion: Different arrangement of thioglycolate (L) and 2-mercaptoglycolate (L') ligands around Au(III) metal core may not be responsible for such different affinities toward synthesized complexes. The increase in sensitivity to gold(III) may imply that these complexes either remain in part as gold(III) species or that one of their metabolites is highly cytotoxic.